OPTIMIZING PUBLIC SERVICES THROUGH THE APPLICATION OF ARTIFICIAL INTELLIGENCE A CASE STUDY OF INTEGRATED ADMINISTRATIVE SERVICES AT THE SUB-DISTRICT LEVEL - Ruhana, Faria; Alimuddin, Asriani; Hidayat, Yogi Syarif; Afrilia, Ufa Anita; Zulfikar, Waluyo (Alqaprint Jatinangor, 2023)
This study explores the optimization of public services through the application of Artificial Intelligence (AI), focusing on a case study of integrated administrative services at the sub-district level. The research aims to understand how AI can enhance the efficiency, accuracy, and accessibility of public services in a local government setting. Employing a mixed-methods approach, the study combines quantitative data analysis of service delivery metrics with qualitative insights from interviews with public officials and service users. The findings reveal that the integration of AI technologies, such as automated data processing, chatbots for customer service, and predictive analytics, significantly improves service delivery times, reduces errors, and increases citizen satisfaction. The study also identifies challenges in implementing AI, including technical infrastructure requirements, staff training needs, and concerns about data privacy and security. The research contributes to the growing body of knowledge on digital transformation in public administration, highlighting the potential of AI to revolutionize local government services. The study concludes with recommendations for policymakers and practitioners on effectively integrating AI into public service frameworks, emphasizing the need for strategic planning, stakeholder engagement, and continuous evaluation.